PENGARUH DEWAN KOMISARIS, DEWAN DIREKSI, KOMITE AUDIT, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Wardati, Safari Dwi; Shofiyah, Shofiyah; Ariani, Kurnia Rina (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2021)
This study aims to determine the effect of the influence of the board of commissioners, board of directors, audit committee, and company size on the company's financial performance. The method used in this research is quantitative method. The population in this study are state-owned companies listed on the Indonesia Stock Exchange during 2014-2020 with a total of 20 companies. Sampling was carried out using purposive sampling technique, the criteria determined were state-owned companies listed on the Indonesia Stock Exchange for the period 2014-2020, companies publishing annual reports successively for the period 2014-2020, which can be accessed through the Indonesia Stock Exchange website (www. idx.co.id) or can be accessed from the website of each company, and the Company publishes all data needed for research analysis. Based on the sample selection process, there were 13 companies that were sampled with a 7 year research period so that the number of samples was 91 samples. The results of this study are the board of directors and the audit committee have an effect on the company's financial performance. Meanwhile, the board of commissioners and the size of the company have no effect on the company's financial performance.